Characterization of cellulolytic microbial consortium enriched on Napier grass using metagenomic approaches - Kanokratana, Pattanop; Wongwilaiwalin, Sarunyou; Mhuantong, Wuttichai; Tangphatsornruang, Sithichoke; Eurwilaichitr, Lily; Champreda, Verawat (Journal of bioscience and bioengineering, 2018)
Energy grass is a promising substrate for production of biogas by anaerobic digestion. However, the conversion efficiency is limited by the enzymatically recalcitrant nature of cellulosic wastes. In this study, an active, structurally stable mesophilic lignocellulolytic degrading microbial consortium (Np-LMC) was constructed from forest compost soil microbiota by successive subcultivation on Napier grass under facultative anoxic conditions. According to tagged 16S rRNA gene amplicon sequencing, increasing abundance of facultative Proteobacteria was found in the middle of batch cycle which was then subsequently replaced by the cellulose degraders Firmicutes and Bacteroidetes along with decreasing CMCase, xylanase, and β-glucanase activity profiles in the supernatant after 5 days of incubation. Anaerobic/facultative bacteria Dysgonomonas and Sedimentibacter and aerobic bacteria Comamonas were the major genera found in Np-LMC. The consortium was active on degradation of the native and delignified grass. Direct shotgun sequencing of the consortium metagenome revealed relatively high abundance of genes encoding for various lignocellulose degrading enzymes in 23 glycosyl hydrolase (GH) families compared to previously reported cellulolytic microbial communities in mammalian digestive tracts. Enzymes attacking cellulose and hemicellulose were dominated by GH2, 3, 5, 9, 10, 26, 28 and 43 in addition to a variety of carbohydrate esterases (CE) and auxiliary activities (AA), reflecting adaptation of the enzyme systems to the native herbaceous substrate. The consortium identified here represents the microcosm specifically bred on energy grass, with potential for enhancing degradation of fibrous substrates in bioenergy industry.